Non-peripheral tetra methoxylated pyrazoline bearing Co-II, Cu-II and (MnCl)-Cl-III phthalocyanines: Syntheses, electrochemistry and spectroelectrochemistry - BUDAK, ÖZLEM; KOCA, ATIF (My University, 2022)
The novel and highly soluble cobalt(II), copper(II) and manganese(III) phthalocyanines ((Pc-Co, Pc-Cu, and Pc-Mn) bearing 3-(5-(3,5-dimethoxyphenyl)-1-phenyl-4,5-dihydro-1H-pyrazol-3-yl)phenol have been synthesized and characterized by FT-IR, NMR, UV-Vis and mass spectroscopic methods. Additionally, electrochemical and spectroelectrochemical properties of these phthalocyanine compounds were investigated. Due to the redox inactivity of the Cu2+ central cation of (Pc-Cu), Pc based reductions and oxidation processes are recorded. [(CoPc2-)-Pc-II]/[(CoPc2-)-Pc-I](1-) and [(CoPc2-)-Pc-II]/[(CoPc2-)-Pc-III](1+) couples for the central metal redox reactions, and [(CoPc2-)-Pc-I](1-)/[(CoPc3-)-Pc-I](2-), [(CoPc3-)-Pc-I](2-)/[(CoPc4-)-Pc-I](3-) and [(CoPc2-)-Pc-III](1+)/[(CoPc1-)-Pc-III](2+) couples for the Pc based reduction and oxidation are observed respectively with (Pc-Co). Like (Pc-Co), (Pc-Mn) also illustrated metal-based reduction processes, [Cl1--(MnPc2-)-Pc-III]/[Cl1--(MnPc2-)-Pc-II](1-) and [Cl1--(MnPc2-)-Pc-II](1-)/[Cl1--(MnPc2-)-Pc-I](2-) in addition to the Pc based [Cl1--(MnPc2-)-Pc-I](2-)/[Cl1--(MnPc3-)-Pc-I](3-), [Cl1--(MnPc3-)-Pc-I](3-) /[Cl1--(MnPc4-)-Pc-I](4-) and [Cl1--(MnPc2-)-Pc-III]/[Cl1--(MnPc1-)-Pc-III](1+) redox couples were also recorded. These redox mechanisms were supported with the characteristic spectral changes observed during the in-situ spectroelectrochemical measurements. Especially metal-based electron transfer changes caused distinct spectral and color changes, which are the desired properties of the complexes for the possible opto-electrochemical applications. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Biochemistry; Bioinorganic Chemistry; Inorganic Chemistry; Natural Sciences; KİMYA, İNORGANİK VE NÜKLEER; Temel Bilimler (SCI); KİMYA, ORGANİK; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, ORGANIC; Kimya (çeşitli); Organik Kimya; Genel Kimya; İnorganik kimya; Fizik Bilimleri; Chemistry (miscellaneous); Organic Chemistry; General Chemistry; Physical Sciences; Syntheses; Pyrazoline; Phthalocyanines; Electrochemistry; Spectroelectrochemistry; MANGANESE PHTHALOCYANINE; SUBSTITUTED COBALT; METAL-FREE; IRON; METALLOPHTHALOCYANINES; GRAPHENE; SENSOR; COMPLEXES; COMPOSITE; BEHAVIOR